PERSEPSI MAHASISWA POLITEKNIK NEGERI SEMARANG TERHADAP PELAYANAN BIDANG KEMAHASISWAAN UNTUK MENINGKATKAN KUALITAS PELAYANAAN PADA MAHASISWA POLITEKNIK NEGERI SEMARANG : PERSEPSI MAHASISWA POLITEKNIK NEGERI SEMARANG TERHADAP PELAYANAN BIDANG KEMAHASISWAAN UNTUK MENINGKATKAN KUALITAS PELAYANAAN PADA MAHASISWA POLITEKNIK NEGERI SEMARANG - Sunindyo, Aris; Fajria, Rola Nurul; Prihatiningsih; Nugraha, Nyata; Kusmargiani, Ida Savitri (Bangun Rekaprima, 2025)
This study aims to evaluate student perceptions of the quality of services provided by the student affairs sector at Politeknik Negeri Semarang. The method used in this research is a survey by distributing questionnaires to 100 active students as respondents. Data analysis was performed using multiple linear regression. The results showed that the dimensions of service quality such as tangible, reliability, responsiveness, and assurance have a significant influence on student satisfaction, while empathy has no significant effect. This study also provides recommendations for improving service quality in the field of student affairs in order to meet student expectations.